Infix in Tolour Language - Paat, R C (Journal of Educational Method and Technology, 2018)
This research is aimed to describe: 1) Form of Infix {um-} in Tondano dialect of Tolour Language, 2) in-the function of infix {-um-} in Tondano dialect of Tolour Language, 3) the meaning of infix {-um-} in Tondano dialect of Tolour Language. This research used quantitative methods. Data collection technique used for this research was trigger (basic technique) and interview (advance technique). Resea2rcher used list of questions that were related to infix problem in Tolour Language. Other than that, in obtaining supporting data, 3 (three) informants from Seretan Village were chosen. Ata analysis technique was undertaken by identifying finding of interview, combined to data from written source. The next step, the data of kind were classified and analyzed according to its form, function and the meaning, the cause of the attachment of infix in the basic form. At the end, the finding from data analysis showed that infix arrangement {-um-} at the basic form had experienced changes. The forms of infix {-um-} in Tondano dialect of Tolour Language cover: (1) if it was attached to the basic form which has vocal (a, i, u, e, o), so the assimilation and position change would happen, (2) if it was attached to the basic form preceded by bilabial phoneme /p,w/, change would happen which was infix {-um-}would move prefix position and the first phoneme in its assimilated form, (3) if it was attached to the basic preceded by consonant phoneme, there would be no change. Infix {-um-} is aimed to form transitive and intransitive verb from basic forms of varied categories either pre-category, nominal, adjective, and numerical. He purpose of infix attachment in its basic form changed according to the purpose of the basic from attached, which (1) means an action that would happen, (2) determines the purpose of an continuous action that related to what is said in the basic form, (3) determines the meaning of becoming like it in the basic form, and (4) determines the meaning of would become as said in the basic form. Keywords: Infix, Tolour Language.